Corporate restructuring activities of Singapore companies prior to listing on the Stock Exchange of Singapore - Neo, Kok Beng (2009)
Successful companies usually seek listing on a stock exchange in order to acquire funds to expand their business. The focus of the study is on Singapore companies prior to their listing on the SES and the aim is to find out whether there is a trend in the corporate restructuring process prior to listing on the SES.